2010
DOI: 10.1111/j.1538-7836.2010.04049.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proton pump inhibitors on clinical outcome in patients treated with clopidogrel: a systematic review and meta‐analysis

Abstract: To cite this article: Siller-Matula JM, Jilma B, Schrö r K, Christ G, Huber K. Effect of proton pump inhibitors on clinical outcome in patients treated with clopidogrel: a systematic review and meta-analysis. J Thromb Haemost 2010; 8: 2624-41.Summary. To investigate whether proton pump inhibitors (PPIs) negatively affect clinical outcome in patients treated with clopidogrel. Systematic review and meta-analysis. Outcomes evaluated were combined major adverse cardiac events (MACE), myocardial infarction (MI), st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 49 publications
(67 reference statements)
4
70
1
Order By: Relevance
“…Studies have shown that high on-treatment platelet reactivity (HPR) is a risk factor for secondary CVEs in patients receiving aspirin and/or clopidogrel treatment [7,8]. Suggested causes of the impaired efficacy of APT are non-compliance, APT intolerance, high platelet turnover, and nonresponse [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that high on-treatment platelet reactivity (HPR) is a risk factor for secondary CVEs in patients receiving aspirin and/or clopidogrel treatment [7,8]. Suggested causes of the impaired efficacy of APT are non-compliance, APT intolerance, high platelet turnover, and nonresponse [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…79 A recent meta-analysis also showed a modest increase in MI but not death. 80 The COGENT (A Prospective, Randomized, Placebo-Controlled Trial of Omeprazole in Patients Receiving Aspirin and Clopidogrel Trial) trial, the only prospective randomized, double-blind comparison of omeprazole versus placebo in patients on aspirin and clopidogrel, showed reduced upper GI bleeding by more than 80% without a significant difference in cardiovascular outcomes. 81 Although there was no apparent cardiovascular interaction between clopidogrel and omeprazole, the trial was not sufficiently powered and thus the results of COGENT cannot rule out a clinically meaningful difference in cardiovascular events due to use of a PPI.…”
Section: Proton Pump Inhibitor Usementioning
confidence: 99%
“…Interestingly, 2 recent meta-analyses of published studies found no association between PPI use and mortality. 32,33 A significant association with cardiovascular events was found in observational studies but not in those using propensity matching or participants of randomized trials. The presence of significant heterogeneity again indicates the biased and confounded nature of the evidence.…”
Section: Ppis and Clopidogrelmentioning
confidence: 99%